Teganai Hegemony Based On Islamic Family Law In Marriage Arrangements In Tanjung Muda Village, Hamparan Rawang District - Eva Susti Kurnia; Widiya Yul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study confirms that teganai is a central element in the social system of the matrilineal community in Tanjung Muda Village which has social, moral, and symbolic functions in maintaining family honor and social balance. Its authority is culturally legitimized and reflects a form of cultural hegemony that society accepts voluntarily. In the perspective of structural functionalism theory, the role of teganai contributes to strengthening solidarity and social stability. However, when such authority goes beyond the boundaries of Islamic law, there is a potential structural dysfunction between customs and religious norms. From the point of view of Islamic family law, the role of teganai is acceptable as long as it does not replace the position of the marriage guardian as the legal pillar of marriage. The tension between customary and Islamic law is not in conflict, but rather shows a complementary relationship between living law and divine law. Therefore, harmonization between customary values and Islamic legal principles is needed to maintain balance, justice, and social order in indigenous peoples based on Islamic values.